2018
DOI: 10.4049/jimmunol.1700901
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stromal Cells Stimulate the Proliferation and IL-22 Production of Group 3 Innate Lymphoid Cells

Abstract: Infusion of mesenchymal stromal cells (MSCs) is a promising and increasingly applied therapy for patients who suffer from a variety of inflammatory diseases, including graft-versus-host disease (GvHD), a common and life-threatening complication after allogeneic hematopoietic stem cell transplantation. The therapeutic effect of MSCs is mainly ascribed to their ability to suppress T cells and to support tissue repair. However, clinical response rates in patients with GvHD are limited to 50%, and the determinants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 45 publications
2
30
1
Order By: Relevance
“…Accumulating evidences have demonstrated that MSCs can regulate T cell proliferation, function, balance T-helper (Th)1 and Th2 activity [69,70], upregulate the functions of regulatory T cells (Tregs) [71], suppress B cell functions [72,73], inhibit natural killer (NK) cell proliferation and function [74], and prevent dendritic cell (DC) maturation and activation [6,57,62]. MSCs can also stimulate proliferation and cytokine secretion in innate lymphoid cells (ILCs), a new family of lymphocyte-like cells, which play an important role in innate defences against pathogens [75,76]. MSCs can regulate their immunomodulatory functions according to the micro-environmental inflammatory conditions.…”
Section: Msc Functionsmentioning
confidence: 99%
“…Accumulating evidences have demonstrated that MSCs can regulate T cell proliferation, function, balance T-helper (Th)1 and Th2 activity [69,70], upregulate the functions of regulatory T cells (Tregs) [71], suppress B cell functions [72,73], inhibit natural killer (NK) cell proliferation and function [74], and prevent dendritic cell (DC) maturation and activation [6,57,62]. MSCs can also stimulate proliferation and cytokine secretion in innate lymphoid cells (ILCs), a new family of lymphocyte-like cells, which play an important role in innate defences against pathogens [75,76]. MSCs can regulate their immunomodulatory functions according to the micro-environmental inflammatory conditions.…”
Section: Msc Functionsmentioning
confidence: 99%
“…Notably, we demonstrate that the large majority of CD56 + CD94cells generated on MSCs were indeed mature RORγt + , IL-22-producing ILC3, whereas this was only the case for a minor subset when generated on murine stroma cells [45]. Of note, co-culturing of MSCs with ex vivo isolated human tonsillar ILC3s was shown to enhance ILC3 proliferation and IL-22 production [51].…”
Section: Discussionmentioning
confidence: 72%
“…Indeed, IL-7 stimulation can induce RORγt expression and play a supportive role in IL-23 mediated IL-22 production in ILC3s (94). Furthermore, in vitro co-culture of IL-7 producing mesenchymal stromal cells (MSCs) with ILC3s led to IL-22 production and enhanced IL-2 induced proliferation of ILC3s (95). This was due to IL-7 derived from MSCs as measured by ELISA (95).…”
Section: Il-7rα In Ilc Homeostasis and Function Il-7 And Ilc Functionmentioning
confidence: 98%
“…Furthermore, in vitro co-culture of IL-7 producing mesenchymal stromal cells (MSCs) with ILC3s led to IL-22 production and enhanced IL-2 induced proliferation of ILC3s (95). This was due to IL-7 derived from MSCs as measured by ELISA (95). IL-7, together with retinoic acid (RA), is also important for homing of ILCs to gut-associated tissues by upregulating ILC3-intrinsic expression of α4β7 and selectin ligands, an effect mediated by IL-7 in T cell homing as well (96,97) (Figure 4).…”
Section: Il-7rα In Ilc Homeostasis and Function Il-7 And Ilc Functionmentioning
confidence: 99%